Self-assembled monolayers and titanium dioxide: From surface patterning to potential applications - Paz, Yaron (Beilstein Journal of Nanotechnology, 2011)
The ability to control the properties of self-assembled monolayers (SAMs) attached to solid surfaces and the rare photocatalytic properties of titanium dioxide provide a rationale for the study of systems comprising both. Such systems can be realized in the form of SAMs grown on TiO2 or, in a complementary manner, as TiO2 grown on SAMs. Accordingly, the current status of knowledge regarding SAMs on TiO2 is described. Photocatalytic phenomena that are of specific relevance to SAMs, such as remote degradation, and cases where SAMs were used to study photocatalytic phenomena, are discussed as well. Mastering of micro-patterning is a key issue en route to a successful assimilation of a variety of titanium dioxide based devices. Accordingly, particular attention is given to the description of a variety of methods and techniques aimed at utilizing the photocatalytic properties of titanium dioxide for patterning. Reports on a variety of applications are discussed. These examples, representing the areas of photovoltaics, microelectronics, microelectromechanics, photocatalysis, corrosion prevention and even biomedicine should be regarded as appetizers paving the way for further studies to be performed.
Keywords: photocatalysis; remote degradation; self-assembled monolayers; titanium dioxide

Bibliography of Work on the Photocatalytic Removal of Hazardous Compounds from Water and Air - Blake, D. M. (National Renewable Energy Laboratory, 1994)

Photodegradation of water pollutants - Halman, M. M. (CRC Press, 1996)

(untitled) - Paz, Y.; Luo, Z.; Rabenberg, L.; Heller, A. (J. Mater. Res., 1995)

(untitled) - Gerischer, H.; Heller, A. (J. Phys. Chem., 1991)

(untitled) - Hoffmann, M. R.; Martin, S. T.; Choi, W.; Bahnemann, D. W. (Chem. Rev., 1995)

(untitled) - Paz, Y. (Solid State Phenom., 2010)

(untitled) - Bahnemann, D. W.; Moeing, J.; Chapman, R. (J. Phys. Chem., 1987)

(untitled) - Cho, Y.; Choi, W.; Lee, C.-H.; Hyeon, T.; Lee, H.-I. (Environ. Sci. Technol., 2001)

(untitled) - Shaham Waldmann, N.; Paz, Y. (J. Phys. Chem. C, 2010)

(untitled) - Muñoz, J.; Domènech, X. (J. Appl. Electrochem., 1990)

(untitled) - Turchi, C. S.; Ollis, D. F. (J. Catal., 1990)

(untitled) - Minero, C. (Catal. Today, 1999)

(untitled) - Fujishima, A.; Rao, T. N.; Tryk, D. A. (J. Photochem. Photobiol., C: Photochem. Rev., 2000)

(untitled) - Li, J.; Zhu, L.; Wu, Y.; Harima, Y.; Zhang, A.; Tang, H. (Polymer, 2006)

(untitled) - Helmy, R.; Fadeev, A. Y. (Langmuir, 2002)

(untitled) - Lee, J. P.; Kim, H. K.; Park, C. R.; Park, G.; Kwak, H. T.; Koo, S. M.; Sung, M. M. (J. Phys. Chem. B, 2003)

(untitled) - Mattigod, S. V.; Fryxell, G. E.; Alford, K.; Gilmore, T.; Parker, K.; Serne, J.; Engelhard, M. (Environ. Sci. Technol., 2005)

(untitled) - Haick, H.; Sagatelian, Y.; Paz, Y. (Langmuir, 2003)

(untitled) - Kim, W.-J.; Kim, S.; Lee, B. S.; Kim, A.; Ah, C. S.; Huh, C.; Sung, G. Y.; Yun, W. S. (Langmuir, 2009)

(untitled) - Brunner, H.; Vallant, T.; Mayer, U.; Hoffmann, H.; Basnar, B.; Vallant, M.; Friedbacher, G. (Langmuir, 1999)

(untitled) - Cohen, S. R.; Naaman, R.; Sagiv, J. (J. Phys. Chem., 1986)

(untitled) - Shin, H.; Wang, Y.; Sampathkumaran, U.; De Guire, M. R.; Heuer, A. H.; Sukenik, C. N. (J. Mater. Res., 1999)

(untitled) - Hozumi, A.; Cheng, D. F.; Yagihashi, M. (J. Colloid Interface Sci., 2011)

(untitled) - Loste, E.; Fraile, J.; Fanovich, M. A.; Woerlee, G. F.; Domingo, C. (Adv. Mater., 2004)

(untitled) - García-González, C. A.; Saurina, J.; Ayllón, J. A.; Domingo, C. (J. Phys. Chem. C, 2009)

(untitled) - Marcinko, S.; Helmy, R.; Fadeev, A. Y. (Langmuir, 2003)

(untitled) - Hofer, R.; Textor, M.; Spencer, N. D. (Langmuir, 2001)

(untitled) - Liu, H.-B.; Venkataraman, N. V.; Spencer, N. D.; Textor, M.; Xiao, S.-J. (ChemPhysChem, 2008)

(untitled) - Brodard-Sevarac, F.; Guerrero, G.; Maquet, J.; Florian, P.; Gervais, C.; Mutin, P. H. (Chem. Mater., 2008)

(untitled) - Chen, Y.; Liu, W.; Ye, C.; Yu, L.; Qi, S. (Mater. Res. Bull., 2001)

(untitled) - Pan, D.; Xu, G.; Wan, J.; Shi, Z.; Han, M.; Wang, G. (Langmuir, 2006)

(untitled) - Hozumi, A.; Kim, B.; McCarthy, T. J. (Langmuir, 2009)

(untitled) - Shin, H.; Collins, R. J.; De-Guire, M. R.; Heuer, A. H.; Sukenik, C. N. (J. Mater. Res., 1995)

(untitled) - Liang, S.; Chen, M.; Xue, Q. (Colloids Surf., A, 2008)

(untitled) - Xiao, Z.; Gu, J.; Huang, D.; Lu, Z.; Wei, Y. (Appl. Surf. Sci., 1998)

(untitled) - Xiao, Z.; Su, L.; Gu, N.; Lu, Z.; Wei, Y. (Thin Solid Films, 1998)

(untitled) - Pizem, H.; Sukenik, C. N.; Sampathkumaran, U.; McIlwain, A. K.; De Guire, M. R. (Chem. Mater., 2002)

(untitled) - Masuda, Y.; Sugiyama, T.; Seo, W. S.; Koumoto, K. (Chem. Mater., 2003)

(untitled) - Desu, S. B. (Mater. Sci. Eng., B, 1992)

(untitled) - Yamabi, S.; Imai, H. (Thin Solid Films, 2003)

(untitled) - Xiang, J.; Zhu, P.; Masuda, Y.; Koumoto, K. (Langmuir, 2004)

(untitled) - Lin, H.; Kozuka, H.; Yoko, T. (Mol. Cryst. Liq. Cryst., 1999)

(untitled) - Lin, H.; Kozuka, H.; Yoko, T. (Thin Solid Films, 1998)

(untitled) - Shin, H.; Collins, R. J.; De-Guire, M. R.; Heuer, A. H.; Sukenik, C. N. (J. Mater. Res., 1995)

(untitled) - Rizza, R.; Fitzmaurice, D.; Hearne, S.; Hughes, G.; Spoto, G.; Ciliberto, E.; Kerp, H.; Schropp, R. (Chem. Mater., 1997)

(untitled) - Shimizu, Y.; Kawanabe, K.; Takao, Y.; Egashira, M. (J. Am. Ceram. Soc., 2001)

(untitled) - Lee, J. P.; Jang, Y. J.; Sung, M. M. (Adv. Funct. Mater., 2003)

(untitled) - Seo, E. K.; Lee, J. W.; Sung-Suh, H. M.; Sung, M. M. (Chem. Mater., 2004)

(untitled) - Haick, H.; Paz, Y. (J. Phys. Chem. B, 2001)

(untitled) - Zemel, E.; Paz, Y. (J. Adv. Oxid. Technol., 2002)

(untitled) - Ghosh-Mukerji, S.; Haick, H.; Paz, Y. (J. Photochem. Photobiol., A: Chem., 2003)

(untitled) - Shemer, G.; Paz, Y. (Int. J. Photoenergy, 2011)

(untitled) - Haick, H.; Paz, Y. (J. Phys. Chem. B, 2003)

(untitled) - Howgate, J.; Schoell, S. J.; Hoeb, M.; Steins, W.; Baur, B.; Hertrich, S.; Nickel, B.; Sharp, I. D.; Stutzmann, M.; Eickhoff, M. (Adv. Mater., 2010)

(untitled) - Tizazu, G.; Adawi, A. M.; Leggett, G. J.; Lidzey, D. G. (Langmuir, 2009)

(untitled) - Jeon, N. L.; Nuzzo, R. G.; Xia, Y.; Mrksich, M.; Whitesides, G. M. (Langmuir, 1995)

(untitled) - Xia, Y.; Whitesides, G. M. (Angew. Chem., Int. Ed., 1998)

(untitled) - Denis, F. A.; Hanarp, P.; Sutherland, D. S.; Dufrêne, Y. F. (Langmuir, 2004)

(untitled) - Ye, T.; Wynn, D.; Dudek, R.; Borguet, E. (Langmuir, 2001)

(untitled) - Nakata, K.; Nishimoto, S.; Yuda, Y.; Ochiai, T.; Murakami, T.; Fujishima, A. (Langmuir, 2010)

(untitled) - Nishimoto, S.; Kubo, A.; Zhang, X.; Liu, Z.; Taneichi, N.; Okui, T.; Murakami, T.; Komine, T.; Fujishima, A. (Appl. Surf. Sci., 2008)

(untitled) - Nishimoto, S.; Sekine, H.; Zhang, X.; Liu, Z.; Nakata, K.; Murakami, T.; Koide, Y.; Fujishima, A. (Langmuir, 2009)

(untitled) - Lee, J. P.; Sung, M. M. (J. Am. Chem. Soc., 2004)

(untitled) - Notsu, H.; Kubo, W.; Shitanda, I.; Tatsuma, T. (J. Mater. Chem., 2005)

(untitled) - Blondiaux, N.; Zürcher, S.; Liley, M.; Spencer, N. D. (Langmuir, 2007)

(untitled) - Bai, Y.; Zhang, Y.; Li, W.; Zhou, X.; Wang, C.; Feng, X.; Zhang, L.; Lu, X. (Appl. Surf. Sci., 2009)

(untitled) - Haick, H.; Paz, Y. (ChemPhysChem, 2003)

(untitled) - Kwon, B. G.; Kwon, J.-H. (J. Ind. Eng. Chem., 2010)

(untitled) - Masuda, Y.; Gao, Y.; Zhu, P.; Shirahata, N.; Saito, N.; Koumoto, K. (J. Ceram. Soc. Jpn., 2004)

(untitled) - Masuda, Y.; Kondo, M.; Koumoto, K. (Cryst. Growth Des., 2009)

(untitled) - Masuda, Y.; Sugiyama, T.; Lin, H.; Seo, W. S.; Koumoto, K. (Thin Solid Films, 2001)

(untitled) - Masuda, Y.; Seo, W. S.; Koumoto, K. (Langmuir, 2001)

(untitled) - Masuda, Y.; Jinbo, Y.; Yonezawa, T.; Koumoto, K. (Chem. Mater., 2002)

(untitled) - Koumoto, K.; Seo, S.; Sugiyama, T.; Seo, W. S.; Dressick, W. J. (Chem. Mater., 1999)

(untitled) - Masuda, Y.; Saito, N.; Hoffmann, R.; De Guire, M. R.; Koumoto, K. (Sci. Technol. Adv. Mater., 2003)

(untitled) - Xiang, J.; Masuda, Y.; Koumoto, K. (Adv. Mater., 2004)

(untitled) - Masuda, Y.; Sugiyama, T.; Koumoto, K. (J. Mater. Chem., 2002)

(untitled) - Collins, R. J.; Shin, H.; De Guire, M. R.; Heuer, A. H.; Sukenik, C. N. (Appl. Phys. Lett., 1996)

(untitled) - Park, M. H.; Jang, Y. J.; Sung-Suh, H. M.; Sung, M. M. (Langmuir, 2004)

(untitled) - Cherniavskaya, O.; Adzic, A.; Knutson, C.; Gross, B. J.; Zang, L.; Liu, R.; Adams, D. M. (Langmuir, 2002)

(untitled) - Shin, H.; Jeong, D.-K.; Lee, J.; Sung, M. M.; Kim, J. (Adv. Mater., 2004)

(untitled) - Bae, C.; Shin, H.; Moon, J.; Sung, M. M. (Chem. Mater., 2006)

(untitled) - Masuda, Y.; Seo, W.-S.; Koumoto, K. (Solid State Ionics, 2004)

(untitled) - Lai, Y.; Huang, J.; Gong, J.; Huang, Y.; Wang, C.; Chen, Z.; Lin, C. (J. Electrochem. Soc., 2009)

(untitled) - O'Regan, B.; Grätzel, M. (Nature, 1991)

(untitled) - Kamat, P. V.; Gevaert, M.; Vinodgopal, K. (J. Phys. Chem. B, 1997)

(untitled) - Shi, Z.; Li, Y.; Wang, S.; Guo, Z.; Du, C.; Xiao, S.; Sun, N.; Cao, Y.; Yao, J.; Zhu, D.; Gao, E.; Cai, S. (Chem. Phys. Lett., 2001)

(untitled) - Chong, S. V.; Suresh, N.; Xia, J.; Al-Salim, N.; Idriss, H. (J. Phys. Chem. C, 2007)

(untitled) - Pan, J.; Xu, Y.; Sun, L.; Sundström, V.; Polívka, T. (J. Am. Chem. Soc., 2004)

(untitled) - Haubner, K.; Jaehne, E.; Adler, H.-J. P.; Koehler, D.; Loppacher, C.; Eng, L. M.; Grezner, J.; Herasimovich, A.; Scheinert, S. (Phys. Status Solidi A, 2008)

(untitled) - Gilmer, D. C.; Colombo, D. G.; Taylor, C. J.; Roberts, J.; Haugstad, G.; Campbell, S. A.; Kim, H.-S.; Wilk, G. D.; Gribelyuk, M. A.; Gladfelter, W. L. (Chem. Vap. Deposition, 1998)

(untitled) - Gao, Y.; Masuda, Y.; Koumoto, K. (Chem. Mater., 2004)

(untitled) - Koumoto, K.; Masuda, Y.; Wang, D. J. (Int. J. Soc. Mater. Eng. Resour., 2002)

(untitled) - Campbell, S. A.; Gilmer, D. C.; Wang, X.-C.; Hsieh, M.-T.; Kim, H.-S.; Gladfelter, W. L.; Yan, J. (IEEE Trans. Electron Devices, 1997)

(untitled) - Shin, H.; De Guire, M. R.; Heuer, A. H. (J. Appl. Phys., 1998)

(untitled) - Shyue, J.-J.; Padture, N. P. (Mater. Lett., 2007)

(untitled) - Majewski, L. A.; Schroeder, R.; Grell, M. (Adv. Funct. Mater., 2005)

(untitled) - Avnon, E.; Paz, Y.; Tessler, N. (Appl. Phys. Lett., 2009)

(untitled) - Ashurst, W. R.; Jang, Y. J.; Magagnin, L.; Carraro, C.; Sung, M. M.; Maboudian, R. (Nanometer-thin titania films with SAM-level stiction and superior wear resistance for reliable MEMS performance, IEEE International Conference on Micro Electro Mechanical Systems, Maastricht, The Netherlands, 25.1.2004-29.1.2004)

(untitled) - Senadeera, G. K. R.; Kitamura, T.; Wada, Y.; Yanagida, S. (J. Photochem. Photobiol., A: Chem., 2004)

(untitled) - Senadeera, G. K. R.; Kitamura, T.; Wada, Y.; Yanagida, S. (J. Photochem. Photobiol., A: Chem., 2006)

(untitled) - Hau, S. K.; Yip, H.-L.; Acton, O.; Baek, N. S.; Ma, H.; Jen, A. K.-Y. (J. Mater. Chem., 2008)

(untitled) - Hsu, C.-W.; Wang, L.; Su, W.-F. (J. Colloid Interface Sci., 2009)

(untitled) - Chong, L.-W.; Chien, H.-T.; Lee, Y.-L. (J. Power Sources, 2010)

(untitled) - Jin-nouchi, Y.; Naya, S.-i.; Tada, H. (J. Phys. Chem. C, 2010)

(untitled) - Ardalan, P.; Brennan, T. P.; Lee, H.-B.-R.; Bakke, J. R.; Ding, I.-K.; McGehee, M. D.; Bent, S. F. (ACS Nano, 2011)

(untitled) - Wang, P.; Zakeeruddin, S. M.; Humphry-Baker, R.; Moser, J. E.; Grätzel, M. (Adv. Mater., 2003)

(untitled) - Nakata, K.; Nishimoto, S.; Kubo, A.; Tryk, D.; Ochiai, T.; Murakami, T.; Fujishima, A. (Chem.–Asian J., 2009)

(untitled) - Nishimoto, S.; Kubo, A.; Nohara, K.; Zhang, X.; Taneichi, N.; Okui, T.; Liu, Z.; Nakata, K.; Sakai, H.; Murakami, T.; Abe, M.; Komine, T.; et al. (Appl. Surf. Sci., 2009)

(untitled) - Naoi, K.; Ohko, Y.; Tatasuma, T. (J. Am. Chem. Soc., 2004)

(untitled) - Naoi, K.; Ohko, Y.; Tatasuma, T. (Chem. Commun., 2005)

(untitled) - Paz, Y. (C. R. Chim., 2006)

(untitled) - Ghosh-Mukerji, S.; Haick, H.; Schvartzman, M.; Paz, Y. (J. Am. Chem. Soc., 2001)

(untitled) - Sagatelian, Y.; Sharabi, D.; Paz, Y. (J. Photochem. Photobiol., A: Chem., 2005)

(untitled) - Baskaran, S.; Song, L.; Liu, J.; Chen, Y. L.; Graff, G. L. (J. Am. Ceram. Soc., 1998)

(untitled) - Yang, Y.; Lai, Y.; Zhang, Q.; Wu, K.; Zhang, L.; Lin, C.; Tang, P. (Colloids Surf., B, 2010)

(untitled) - Meth, S.; Savchenko, N.; Koltypin, M.; Starosvetsky, D.; Viva, F. A.; Groysman, A.; Sukenik, C. N. (Corros. Sci., 2010)